Beyond the centre : decentralizing the state - Burki, Shahid Javed (World Bank WashingtonUS, 1999)
Finds that the impact of decentralization - its effect on the efficiency of public services, on equity, and on macroeconomic stability - depends very much on the specifics of the case. Stresses the imprtance of accountability as well as the authority to deliver results.